Invasive micropapillary carcinoma of urinary bladder: A clinicopathological study - Debajyoti Chatterjee; Ashim Das; Bishan D Radotra (Wolters Kluwer Medknow Publications, 2015)
Context: Micropapillary variant of urothelial carcinoma (MPUC) is a rare but well-recognized tumor of the urinary bladder. Tumors with micropapillary areas accompanying conventional urothelial carcinoma are more aggressive compared to conventional urothelial carcinoma and show variable keratin 7, keratin 20 and human epidermal growth factor receptor 2 (Her 2)neu expression. Aim: The aim of the study was to analyze the clinical, morphological and immunohistochemical profile of MPUC. Materials and Methods: Transurethral resection of bladder tumor (TURBT) chips of seven cases of invasive MPUC with subsequent cystoprostatectomy specimens of five patients was reviewed. Epithelial membrane antigen (EMA), Keratin 7, Keratin 20, and Her 2 immunohistochemistry were performed in all cases. Follow-up information was available for all patients (2-36 months). Results: All seven patients were male, and their ages ranged from 50 to 62 years. All cases presented with hematuria. The micropapillary pattern was seen in 20-95% of the tumor. All cases showed extensive lymphatic emboli with detrusor muscle invasion. Lymph node metastasis was present in all cases undergoing cystoprostatectomy except one. Keratin 7 and abluminal pattern of EMA positivity were seen in all cases. Keratin 20 was positive in five cases (71%), and Her 2neu positivity was seen in four cases. Three patients died 2, 3, and 6 months after initial diagnosis, among which two were Her 2 positive and one was Her 2 negative. There was no clear prognostic significance of Her 2 positivity. Conclusion: (1) MPUC is a rare but highly aggressive tumor. (2) Micropapillary is usually the predominant pattern. (3) Keratin 7 is expressed universally, whereas Keratin 20 expression is variable. (4) Her 2 expression has no clear influence on the survival.